Evaluating the Performance of Balance Physiotherapy Exercises Using a Sensory Platform: The Basis for a Persuasive Balance Rehabilitation Virtual Coaching System - Tsakanikas, Vassilios D.; Gatsios, Dimitrios; Dimopoulos, Dimitrios; Pardalis, Athanasios; Pavlou, Marousa; Liston, Matthew B.; Fotiadis, Dimitrios I. (Frontiers in Digital Health, 2020)
Rehabilitation programs play an important role in improving the quality of life of patients with balance disorders. Such programs are usually executed in a home environment, due to lack of resources. This procedure usually results to poorly performed exercises or even complete drop outs from the programs, as the patients lack of guidance and motivation. This paper introduces a novel system for managing balance disorders in a home environment using a virtual coach for guidance, instruction and inducement. The proposed system comprises sensing devices, augmented reality technology and intelligent inference agents which capture, recognize and evaluate a patient's performance during the execution of exercises. More specifically, this work presents a home based motion capture and assessment module which utilize a sensory platform to recognize an exercise performed by a patient and assess it. The sensory platform comprise IMU sensors (Mbientlab MMR 9axis), pressure insoles (Moticon) and a depth RGB camera (IntelD415). This module is designed to deliver messages both during the performance of the exercise, delivering personalized notifications and alerts to the patient and after the end of the exercise, scoring the overall performance of the patient. A set of proof of concept validation studies has been deployed, aiming to assess the accuracy of the different components for the sub-modules of the motion capture and assessment module. More specifically, Euler angle calculation algorithm in 2D (R^2=0.99) and in 3D (R^2=0.82 in yaw plane and R^2=0.91 for the pitch plane), as well as head turns speed (R^2=0.96) showed good correlation between the calculated and ground truth values provided be experts' annotations. The posture assessment algorithm resulted to accuracy=0.83 while the gait metrics were validated against two well established gait analysis systems (R^2=0.78 for double support, R^2=0.71 for single support, R^2=0.80 for step time, R^2=0.75 for stride time and R^2=0.82 for cadence). Validation results provided evidence that the proposed system can accurately capture and assess a physiotherapy exercise within the balance disorders context, thus providing a robust basis for the virtual coaching ecosystem and thereby improve a patient's commitment to rehabilitation programs while enhancing the quality of the performed exercises.